2017
DOI: 10.1007/s10096-017-3068-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic accuracy of SIRS criteria, qSOFA score and GYM score for 30-day-mortality in older non-severely dependent infected patients attended in the emergency department

Abstract: The aim of this study was to determine the accuracy of systemic inflammatory response syndrome (SIRS), quick Sepsis-related Organ Failure Assessment (qSOFA) score and GYM score to predict 30-day mortality in older non-severely dependent patients attended for an episode of infection in the emergency department (ED). We performed an analytical, observational, prospective cohort study including patients 75 years of age or older, without severe functional dependence, attended for an infectious process in 69 Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 18 publications
3
28
2
1
Order By: Relevance
“…A number of tools have been suggested to risk‐stratify patients with sepsis (Table ); however, their prognostic performance is lower in older age groups . In older persons, Systemic Inflammatory Response Syndrome (SIRS) criteria and the quick Sepsis‐related Organ Failure Assessment (qSOFA) demonstrate a sensitivity for prediction of 30 day mortality of only 65% and 28%, respectively, using cut‐points of ≥2 . However, qSOFA has a significantly higher specificity than SIRS, at 94% and 49% for 30 day mortality, respectively .…”
Section: Risk Stratification and Prognostication Of Older Patients Wimentioning
confidence: 99%
See 3 more Smart Citations
“…A number of tools have been suggested to risk‐stratify patients with sepsis (Table ); however, their prognostic performance is lower in older age groups . In older persons, Systemic Inflammatory Response Syndrome (SIRS) criteria and the quick Sepsis‐related Organ Failure Assessment (qSOFA) demonstrate a sensitivity for prediction of 30 day mortality of only 65% and 28%, respectively, using cut‐points of ≥2 . However, qSOFA has a significantly higher specificity than SIRS, at 94% and 49% for 30 day mortality, respectively .…”
Section: Risk Stratification and Prognostication Of Older Patients Wimentioning
confidence: 99%
“…In older persons, Systemic Inflammatory Response Syndrome (SIRS) criteria and the quick Sepsis‐related Organ Failure Assessment (qSOFA) demonstrate a sensitivity for prediction of 30 day mortality of only 65% and 28%, respectively, using cut‐points of ≥2 . However, qSOFA has a significantly higher specificity than SIRS, at 94% and 49% for 30 day mortality, respectively . The Glasgow tachYpnoea Morbidity score has recently been suggested as a measure to improve prognostic capacity in older people with sepsis, with a sensitivity of 80% for 30 day mortality when using a cut‐point of ≥1 .…”
Section: Risk Stratification and Prognostication Of Older Patients Wimentioning
confidence: 99%
See 2 more Smart Citations
“…In this meta-analysis, 35 studies with 269,544 patients reported on the prognostic accuracy of the qSOFA and short-term mortality, including 27 retrospective studies [5][6][7][8]10,11,[13][14][15][16]18,20,22,[24][25][26][27]29,[32][33][34][35][37][38][39][40] , while 8 studies were prospective studies 9,12,17,19,21,23,28,30,36 . Due to the heterogeneity of the inclusion criteria, a random-effects model was used to calculate the pooled sensitivity and specificity of the included studies.…”
Section: The Qsofa and Short-term Mortalitymentioning
confidence: 99%